2016
DOI: 10.4018/ijdet.2016040106
|View full text |Cite
|
Sign up to set email alerts
|

Automatic Detection of Tutoring Styles Based on Tutors' Behavior

Abstract: In e-learning systems, tutors have a significant impact on learners' life to increase their knowledge level and to make the learning process more effective. They are characterized by different features. Therefore, identifying tutoring styles is a critical step in understanding the preference of tutors on how to organize and help the learners. In this context, the authors address the problem of extracting tutoring styles from tutors' behavior. According to this later, tutors are classified automatically into th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…Distance teaching now needs a reorganisation of methods and contents instead of a mere transposition of traditional teaching methods and modalities onto virtual classroom platforms [34]. Thus, a good analysis of facilitators' lesson presentation activities is very important in relation to predicting their lesson presentation styles [38,39]. A study by [40] in New Zealand among 32 secondary teachers found that teachers used multiple inquiry-based presentation methods such as flipped learning, knowledge-building pedagogies, and collaboration with both synchronous and asynchronous communication technologies.…”
Section: Online Intentionsmentioning
confidence: 99%
“…Distance teaching now needs a reorganisation of methods and contents instead of a mere transposition of traditional teaching methods and modalities onto virtual classroom platforms [34]. Thus, a good analysis of facilitators' lesson presentation activities is very important in relation to predicting their lesson presentation styles [38,39]. A study by [40] in New Zealand among 32 secondary teachers found that teachers used multiple inquiry-based presentation methods such as flipped learning, knowledge-building pedagogies, and collaboration with both synchronous and asynchronous communication technologies.…”
Section: Online Intentionsmentioning
confidence: 99%
“…The latter can intervene to answer all different questions asked from the part of the enrollers whether they are pedagogical, social, administrative, technical, etc. (Bendjebar et al, 2016). Moreover, the process involves real identification of the participants' categories and their exact level/situation (very serious situation, serious situation, rather serious situation, etc.…”
Section: Introductionmentioning
confidence: 99%